Callimachus - Rawles, Richard (Ancients in action, 2019)
Callimachus was one of the most important Greek poets, and can also be one of the most rewarding to read. He was a pivotal figure in the history of ancient literature and an influential presence in later ancient poetry, including Catullus and Vergil. Yet his work is not read and enjoyed as much as it could be. This new volume in the popular Ancients in Action series seeks to bring Callimachus to a wide audience, addressing the problems with currently available scholarship, which assumes a professional level of expertise, including full knowledge of Greek. Rawles presents a much-needed introduction to Callimachus' poetry and is intended for the non-specialist reader and student, assuming no knowledge of Greek. The book is organised in thematic chapters, rich in quotation (in translation), with selective annotations and guidance for further study and reading.